houstonarmon
houstonarmon
17-10-2020
Mathematics
contestada
6x - 7 y = -1 solve using elimination
Respuesta :
scamblergeorgia
scamblergeorgia
17-10-2020
Answer:
6x_7=-1
+7 +7
6x=6
÷6 ÷6
x=1
Step-by-step explanation:
shown above
Answer Link
VER TODAS LAS RESPUESTAS ( 34+ )
ACCESS MORE
Otras preguntas
Proof: Given: Isosceles trapezoid TRAP with TR=PA Prove: Angle RTA = angle APR
Proof: Given: Isosceles trapezoid TRAP with TR=PA Prove: Angle RTA = angle APR
Proof: Given: Isosceles trapezoid TRAP with TR=PA Prove: Angle RTA = angle APR
In the step by step simplification of expression below which property is not used? 3(1+x)3(x+1)3(x)+3(1)3x +3 A) associative B) commutative C) distributive D)
i need with math it say the ride-it store rents bicycles. the cost is $8.50 for 1 hour, $13.64 for 2 hours, $18.80 for 3 hours, and 23.95 for 4 hours. if the pa
You have a piece of wood that is 7 3/4 feet long. You want to cut one piece that is 3 7/12 feet long and one piece that is 4 1/12 feet long. Do you have enou
Proof: Given: Isosceles trapezoid TRAP with TR=PA Prove: Angle RTA = angle APR
A laptop computer is priced at $650. If the sales tax is 5%, find the total cost of the computer, including sales tax.
Proof: Given: Isosceles trapezoid TRAP with TR=PA Prove: Angle RTA = angle APR
In the step by step simplification of expression below which property is not used? 3(1+x)3(x+1)3(x)+3(1)3x +3 A) associative B) commutative C) distributive D)